A High‐Valent Non‐Heme μ‐Oxo Manganese(IV) Dimer Generated from a Thiolate‐Bound Manganese(II) Complex and Dioxygen. Issue 28 (9th June 2017) - Brazzolotto, Deborah; Cantú Reinhard, Fabián G.; Smith‐Jones, Julian; Retegan, Marius; Amidani, Lucia; Faponle, Abayomi S.; Ray, Kallol; Philouze, Christian; de Visser, Sam P.; Gennari, Marcello; Duboc, Carole
Abstract: This study deals with the unprecedented reactivity of dinuclear non‐heme Mn II –thiolate complexes with O2, which dependent on the protonation state of the initial Mn II dimer selectively generates either a di‐μ‐oxo or μ‐oxo‐μ‐hydroxo Mn IV complex. Both dimers have been characterized by different techniques including single‐crystal X‐ray diffraction and mass spectrometry. Oxygenation reactions carried out with labeled 18 O2 unambiguously show that the oxygen atoms present in the Mn IV dimers originate from O2 . Based on experimental observations and DFT calculations, evidence is provided that these Mn IV species comproportionate with a Mn II precursor to yield μ‐oxo and/or μ‐hydroxo Mn III dimers. Our work highlights the delicate balance of reaction conditions to control the synthesis of non‐heme high‐valent μ‐oxo and μ‐hydroxo Mn species from Mn II precursors and O2 . Abstract : Thiolate is the key : Dinuclear Mn II –thiolate complexes display an unprecedented reactivity: direct O2 activation to generate dinuclear high‐valent oxo Mn species, including a di‐μ‐oxo Mn IV dimer. Depending on the experimental conditions, the oxidized Mn species are different. A mechanism based on theoretical calculations is discussed to rationalize all experimental data.